Stereotyp nazwisk polskich w dwudziestoleciu międzywojennym = The stereotype of polish surnames in the interwar period of the polish 20th century history - Woźniak, Ewa; Zarębski, Rafał (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The authors deal with the problem of the stereotype of surnames ending in -ski in the interwar period. The study is based on varied examples of the change of surnames: those recorded by linguists and laymen, and those found in literature and in official applications for the change of surname. The analysis questions the common at the time judgement that adopting surnames ending in -ski indicated aspiration to noble origin.
Keywords: nazwisko; stereotypy; Polska międzywojenna; zmiana nazwisk; surname; stereotypes; Inter-war Poland; change of surnames